Studies of the genetics and physiology of a nitrate non-utilizing strain of Neurospora - R. M. Blakely; A. M. Srb (Fungal Genetics Reports, 1962)
Studies of the genetics andphysiology of a nitrate non-utilizing strain of Neurospora